The track of sand - Camilleri, Andrea (Camilleri, Andrea. Inspector Montalbano mystery., 2010)
Montalbano wakes from strange dreams to find a gruesomely bludgeoned horse carcass in front of his seaside home. When his men come to investigate, the carcass disappears, leaving only a trail in the sand. Before long, two people report missing horses - Rachele, a champion equestrian, an Lo Duca, one of the richest men in Sicily. Then Montalbano's home is broken into and is ransacked and he is certain that the crimes are linked. As he negotiates the glittering underworld of legitimate horseracing and the Mafia's connection to it, the scrupulous and melancholy Montalbano is aided by his unorthodox methods, melancholy self-reflection, and love of good food--Cover.